An oceanographic and climatological atlas of Brisol Bay - Wise, James L.; LaBelle, Joseph C.; Leslie, Lynn D.; Arctic Environmental Information and Data Center (Alaska); United States. Coast Guard. Office of Engineering and Development. (Washington, DC : U.S. Coast Guard, Office of Engineering and Development, 1988)
"October 1987." Cover title. Bibliography: p. 182-185. Final report. Mode of access: Internet.